NAADP receptors. - Galione, A; Ruas, M (2005)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is a recently described Ca2+ mobilizing messenger. First described in the sea urchin egg, it has been shown to mobilize Ca2+ from intracellular stores. It is a remarkably potent molecule, and recent reports show that its cellular levels change in response to a variety of agonists confirming its role as a Ca2+ mobilizing messenger. In many cases NAADP interacts with other Ca2+ mobilizing messengers such as inositol 1,4,5 trisphosphate (IP3 and cyclic adenosine diphosphate ribose (cADPR) in shaping cytosolic Ca2+ signals. What is not clear is the molecular nature of the NAADP-sensitive Ca2+ release mechanism and its sub-cellular localization. In this review we focus on the recent progress made in sea urchin eggs, which indicates that NAADP activates a novel Ca2+ release channel distinct from the relatively well-characterized IP3 and ryanodine receptors. Furthermore, in the sea urchin egg, the NAADP-sensitive store appears to be separate from the endoplasmic reticulum (ER) and is most likely an acidic store. These findings have also been reinforced by similar findings by some in mammalian cells. Finally, we discuss ongoing strategies to characterise NAADP-binding proteins which will greatly enhance our understanding of NAADP-mediated Ca2+ signalling, and lead to the development of more selective tools to probe the role of this messenger.